The Impact of Work Climate and Burnout on Employee Performance with Job Satisfaction as a Mediating Variable : Evidence from North Medan Samsat - Firmansyah; Batubara, Soulthan Saladin; Rindi Andika (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The focus of this study is to analyze job satisfaction in mediating the relationship between work climate and burnout on employee performance. A quantitative approach was chosen for this research, with data collected through the distribution of questionnaires to 74 employees at Samsat Medan Utara. Data analysis was conducted using Structural Equation Modeling (PLS SEM). The results show that at Samsat Medan Utara, the work environment has a direct effect on job satisfaction. The work environment directly influences employee performance. Burnout has no direct effect on job satisfaction. Job satisfaction has a direct effect on employee performance. Job satisfaction also indirectly mediates the influence of work climate on employee performance. However, job satisfaction does not significantly mediate the effect of burnout on employee performance.